2017
DOI: 10.1016/j.mcn.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Membrane shaping by actin and myosin during regulated exocytosis

Abstract: The cortical actin network in neurosecretory cells is a dense mesh of actin filaments underlying the plasma membrane. Interaction of actomyosin with vesicular membranes or the plasma membrane is vital for tethering, retention, transport as well as fusion and fission of exo-and endocytic membrane structures. During regulated exocytosis the cortical actin network undergoes dramatic changes in morphology to accommodate vesicle docking, fusion and replenishment. Most of these processes involve plasma membrane Phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 88 publications
(50 reference statements)
1
31
0
Order By: Relevance
“…In this paper we asked if is there was any remodeling of the spectrin skeleton during the ageing in vivo of RBCs, under the hypotheses that if they released spectrin-free vesicles as a basic mechanism to decrease in surface area, this would automatically result in an excess of spectrin within the cell. What we actually found is that apparently such an imbalance never arises during RBC life in the circulation, as not only the cell loses membrane surface area, but also spectrin and other components of the membrane skeleton [11]. To account for the spectrin decline we wondered whether this could be achieved through proteolysis and investigated whether vestiges of such process could exist in the form of spectrin fragments in the RBCs of progressively older age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we asked if is there was any remodeling of the spectrin skeleton during the ageing in vivo of RBCs, under the hypotheses that if they released spectrin-free vesicles as a basic mechanism to decrease in surface area, this would automatically result in an excess of spectrin within the cell. What we actually found is that apparently such an imbalance never arises during RBC life in the circulation, as not only the cell loses membrane surface area, but also spectrin and other components of the membrane skeleton [11]. To account for the spectrin decline we wondered whether this could be achieved through proteolysis and investigated whether vestiges of such process could exist in the form of spectrin fragments in the RBCs of progressively older age.…”
Section: Discussionmentioning
confidence: 99%
“…One natural question was, therefore, whether old RBCs still contain the original endowment of spectrin and other membrane skeletal proteins that was present at the reticulocyte stage [10]. We have recently observed that this is not the case, and that spectrin is subjected to a decrease of approximately the same extent as the decrease in surface area that was described to occur in old RBCs [11]. While holding as true the (undemonstrated) hypotheses that spectrin could not be lost in vivo with supposedly spectrin-free vesicles, we asked whether a process could exist that targets spectrin dimers and/or tetramers for degradation as soon as they dissociate from the portions of lipid bilayer that are lost with the vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results indicate that JMY expression is not required for plasma membrane internalization but it is essential for endocytosed vesicle trafficking into early endosomes. Notably, the actin cytoskeleton is reported to play an important and variable role in vesicular transport (Liu, 2016; Papadopulos, 2017). This realization supports the notion that JMY induced vesicle trafficking is mediated through JMY interacting with the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the F-actin cytoskeleton and the plasma membrane affects the dynamics of exo-and endocytic membranes (Guti errez, 2012;Meunier & Guti errez, 2016;Papadopulos, 2017). Prior work has shown that the microtubule cytoskeleton plays crucial roles in infection thread growth, infection droplet formation and bacterial release (Kitaeva et al, 2016).…”
Section: The Actin Cytoskeleton Forms Distinct Spatial Organizations mentioning
confidence: 99%